Correlation of Surface Toll-Like Receptor 9 Expression with IL-17 Production in Neutrophils during Septic Peritonitis in Mice Induced by E. coli. (25th February 2016) - Ren, Yunjia; Hua, Li; Meng, Xiuping; Xiao, Yue; Hao, Xu; Guo, Sheng; Zhao, Peiyan; Wang, Luowei; Dong, Boqi; Yu, Yongli; Wang, Liying
Abstract : IL-17 is a proinflammatory cytokine produced by various immune cells. Polymorphonuclear neutrophils (PMNs) are the first line of defense in bacterial infection and express surface Toll-like receptor 9 (sTLR9). To study the relationship of sTLR9 and IL-17 in PMNs during bacterial infection, we infected mice with E. coli intraperitoneally to establish a septic peritonitis model for studying the PMNs response in peritoneal cavity. We found that PMNs and some of "giant cells" were massively accumulated in the peritoneal cavity of mice with fatal septic peritonitis induced by E. coli . Kinetically, the CD11b + PMNs were increased from 20–40% at 18 hours to >80% at 72 hours after infection. After E. coli infection, sTLR9 expression on CD11b + and CD11b − PMNs and macrophages in the PLCs were increased at early stage and deceased at late stage; IL-17 expression was also increased in CD11b + PMNs, CD11b − PMNs, macrophages, and CD3 + T cells. Using experiments of in vitro blockage, qRT-PCR and cell sorting, we confirmed that PMNs in the PLCs did increase their IL-17 expression during E. coli infection. Interestingly, sTLR9 − CD11b + Ly6G + PMNs, not sTLR9 + CD11b + Ly6G + PMNs, were found to be able to increase their IL-17 expression. Together, the data may help understand novel roles of PMNs in septic peritonitis.